2005
DOI: 10.1097/01.mao.0000169791.53201.e1
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Of Hearing Loss In A Rat Model Of Cochlear Implantation Trauma

Abstract: These results document a progressive loss of hearing acuity postimplantation and strongly suggest that electrode insertion trauma generated oxidative stress within injured cochlear tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 21 publications
7
63
0
1
Order By: Relevance
“…In the rat, Eshraghi et al [2005] found an immediate frequency-independent hearing loss of approximately 30 dB, increasing to 50 dB over the subsequent month following the insertion and immediate removal of a rigid implant electrode. These researchers have reported limited data from guinea pigs receiving the same cochlear trauma, which reveals a somewhat lower hearing loss of on average 15.6 dB, increasing by another 13.6 dB through a progressive hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rat, Eshraghi et al [2005] found an immediate frequency-independent hearing loss of approximately 30 dB, increasing to 50 dB over the subsequent month following the insertion and immediate removal of a rigid implant electrode. These researchers have reported limited data from guinea pigs receiving the same cochlear trauma, which reveals a somewhat lower hearing loss of on average 15.6 dB, increasing by another 13.6 dB through a progressive hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery may cause unique types of inner ear trauma, including drilling and hydraulic pressure trauma, loss of perilymph and direct and sudden injury to inner ear structures. A rat model of cochlear implant trauma, created by the insertion and immediate withdrawal of a 'model' cochlear implant electrode, is characterized by an immediate followed by a progressive hearing loss [Eshraghi et al, 2005]. With this model, both the immediate and the delayed hearing loss were diminished by hypothermia, and in a guinea pig model the delayed hearing loss was reduced by a week-long perfusion of the scala tympani with the antiapoptotic agent D-JNKI-1 [Eshraghi et al, , 2007 .…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear if the onset of post-operative hearing loss is immediate or occurs over hours to days, although Adunka et al [49] documented preserved cochlear microphonics immediately after cochlear implant insertion in a patient who subsequently developed a profound hearing loss in the operated ear, suggesting that ‘factors other than immediate changes induced by implant insertion were likely responsible’. There are several mechanisms by which hearing loss may progress rapidly, including oxidative stress to the hair cells [34,39,50,51,52,53,54,55] (which has been observed at regions distant to the site of physical trauma), inflammation [34,36,56,57,58,59,60,61], loss of the endocochlear potential though disruption of the lateral cochlear wall [55,62,63,64] and potassium toxicity through admixing of the perilymph and endolymph due to disruption of the basilar or Reissner’s membrane [65]. The endocochlear potential can recover following some types of trauma, such as ototoxicity [62,63], as can the putative membranous tears tentatively implicated with endolymphatic hydrops, leading to an improvement in hearing.…”
Section: Discussionmentioning
confidence: 99%
“…When a delayed elevation of hearing thresholds does occur, it is thought to be due to intracochlear infection, acute inflammatory changes within the inner ear or healing by fibrous tissue formation and/or new bone growth. Recently, there has been experimental evidence to suggest that one mechanism associated with delayed hearing loss may be oxidative stress [Eshraghi et al, 2005]. RW perforation does not permanently affect hearing and the spontaneous healing of the membrane may make it a good alternative to cochleostomy for direct intracochlear perfusion [Lamm et al, 1986].…”
Section: Accessing Cochlear Fluidsmentioning
confidence: 99%